Investigating the Influence of Group Work on Knowledge-building and Application Among Economics Students at Tertiary Level - Kiat Sing, Heng (University of Malaysia, Sarawak, 2024)
Previous studies in economics education have identified gaps between students' engagement in constructing knowledge and their ability to apply it in the real world. Recent work suggests that transforming the conventional economics classroom into an active and student-focused learning environment is highly recommended. Upon closer examination of past studies, it was discovered that they were grounded in Sociocultural and Social Constructivism Theories, focusing on active and social engagement within the learning process. This recognition of student engagement with group members and the development of essential skills for navigating real-world complexities underpin these studies. Hence, group work emerges as a recommended strategy to enhance the student learning experience, aligning with the demands of future professional settings. This study uses a qualitative research design and strict trustworthiness criteria at a selected university to explore how students' epistemological engagement impacts their real-world knowledge application. This data highlights how 86 participants collaborated on a group assessment, revealing insights into their knowledge-building experiences. A teaching and learning model for effective knowledge application in economics is recommended, contributing to the theoretical, epistemological, and practical significance relevant to teaching and learning economics. Future studies can broaden the inquiry by expanding data collection to other higher-level institutions, including other business subjects, and conducting a comparative analysis between experimental and control groups in economics.